Can someone write a solution?

Let x x and y y be whole numbers such that

( x 2 ) 4 x 4 = y 3 . (x-2)^4-x^4=y^3.

How many pairs ( x , y ) (x,y) satisfy the equation?

0 1 2 3 4

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

4 solutions

Gaurav Manwani
Aug 17, 2017

Factorize LHS as Difference of Squares, to obtain the following expression,

8 ( x 2 2 x + 2 ) ( 1 x ) = y 3 8(x^2-2x+2)(1-x)=y^3 \; \quad

As it can be seen, for x , y W x,y \in \mathbb{W} , \quad

x x can only equal 1 1 so that the LHS stays non-negative ; and consequently y = 0 y=0 . \quad

( 1 , 0 ) \therefore (1,0) is the only solution.

I'm not sure I follow this. X=1 leads to both sides becoming zero. Can you elaborate on how you were able to rule out other values of y so easily?

It feels like y=2 and y=4 should yield solutions for example

Nick Wood - 3 years, 5 months ago

Log in to reply

Neither do I. For I can see no restriction on the negativity of y and therefore y cube. How come LHS should stay non-negative?

寅生 魏 - 1 year, 7 months ago

nice solution :)

Bloons Qoth - 2 years, 8 months ago

Just a little add-on:

x 2 2 x + 2 = ( x 1 ) 2 + 1 0 x^2 - 2x + 2 = (x - 1)^2 + 1 ≥ 0

To make the LHS positive,

1 x 0 1 - x ≥ 0

1 x 1 ≥ x

x = 0 x = 0 doesn't yield a cube, so the only whole number solution is x = 1 x = 1

Shubhrajit Sadhukhan - 7 months ago
John 10086
Sep 19, 2018

Firts we factorize ( x 2 ) 2 x 4 (x-2)^2 - x^4

( x 2 ) 2 x 4 (x-2)^2 - x^4

= ( x 2 ) 2 + x 2 ) ( ( x 2 ) 2 x 2 ) (x-2)^2 + x^2)((x-2)^2 - x^2)

= ( x 2 + x ) ( x 2 x ) ( ( x 2 ) 2 + x 2 ) (x-2+x)(x-2-x)((x-2)^2 + x^2)

= ( 2 x 2 ) ( 2 ) ( 2 x 2 2 x + 4 ) (2x-2)(-2)(2x^2-2x+4)

= ( 8 ) ( x 1 ) ( x 2 2 x + 2 ) (-8)(x-1)(x^2-2x+2)

= ( 2 ) 3 ( x 1 ) ( ( x 1 ) 2 + 1 ) -(2)^3 (x-1)((x-1)^2 +1)

Since -8 is already a cube then that means that ( x 1 ) ( ( x 1 ) 2 + 1 ) (x-1)((x-1)^2 +1) must also be a cube hence

( x 1 ) ( ( x 1 ) 2 + 1 ) = k 3 (x-1)((x-1)^2 +1) = k^3

since ( x 1 ) (x-1) and ( ( x 1 ) 2 + 1 ) ((x-1)^2 +1) Z \in \mathbb{Z} We can split this into 4 cases:

Case 1

x 1 = k x-1=k

( x 1 ) 2 + 1 = k 2 (x-1)^2+1=k^2

Case 2

x 1 = k 2 x-1=k^2

( x 1 ) 2 + 1 = k (x-1)^2+1=k

Case 3

x 1 = 1 x-1=1

( x 1 ) 2 + 1 = k 3 (x-1)^2+1=k^3

Case 4

x 1 = k 3 x-1=k^3

( x 1 ) 2 + 1 = 1 (x-1)^2+1=1

Solving the equations we find that the only possible solution is x = 1 x=1 and k = 0 k=0 :

( 8 ( k 3 ) = y 3 (-8(k^3)=y^3

( 0 ) = y 3 (0)=y^3

y = 0 y=0

So the only pair that satisfies this equation is ( 0 ; 1 ) (0;1)

If k is not prime, more cases could be included. For example if k is a even number, let k=2t. Then RHS=8t^3, which can be further split into case 5: x-1 =4t , (x-1)^2+1=2t^2, etc. So this proof is erroneous.

寅生 魏 - 1 year, 7 months ago
Des Con
Aug 1, 2020

( x 2 ) 4 x 4 = y 3 (x-2)^4-x^4=y^3 We can factor this to give ( 2 ) 3 ( x 1 ) ( ( x 1 ) 2 + 1 ) = y 3 (-2)^3(x-1)((x-1)^2+1)=y^3

Since we have ( 2 ) 3 (-2)^3 on the left, the other factors must also give a cube, so ( x 1 ) ( ( x 1 ) 2 + 1 ) = z 3 (x-1)((x-1)^2+1)=z^3

But x 1 x-1 and ( x 1 ) 2 + 1 (x-1)^2+1 are clearly coprime, and the only way for coprime values to multiply to give a cube is if they are both cubes themselves. This tells us that

x 1 = n 3 x-1=n^3

( x 1 ) 2 + 1 = m 3 (x-1)^2+1=m^3

Substituting x 1 = n 3 x-1=n^3 into the second equation gives

n 6 + 1 = m 3 n^6+1=m^3

And so

1 = m 3 n 6 = ( m n 2 ) ( m 2 + m n 2 + n 4 ) 1=m^3-n^6=(m-n^2)(m^2+mn^2+n^4)

Since the two factors on the right are both integers, they must be ± 1 \pm1 .

However m > 0 m>0 by our definition of m m , which tells us the rightmost factor is positive and so both factors equal 1 1 , but since m > 0 m>0 this can only only happen when m = 1 , n = 0 m=1, n=0 . Therefore the other solution is

x 1 = 0 x = 1 x-1=0\implies x=1 .

(x-2)^4 - x^4 = y^3 Or, y^3 = -2 (2x-2)(2x^2 - 4x +4) =-8 (x-1)(x^2 - 2x + 2) =(-2)^3×[(x-1)(x^2 - 2x + 2)] Therefore, for x and y to be whole number (x-1)(x^2 - 2x + 2) has to be perfect cube (x-1)(x^2 - 2x + 2)=(x-1)^3 + (x-1) Therefore (x-1)(x^2 - 2x + 2) to be whole cube x-1 has to be equal to zero as (x-1)^3 is a perfect cube. Therefore x-1=0 x=1 This the only solution for which (x,y) are whole numbers. Therefore there is only 1 solution. (x,y) = (1,0)

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...